2015
DOI: 10.17795/semj23866
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Screening in Primary School Children in Yazd, Iran

Abstract: Background: Urinary screening program for asymptomatic urinary abnormalities among primary school children may facilitate preventing, halting, and deferring the progression of some diseases. Objectives: To describe the urine examination findings in healthy primary school beginners in Yazd (Iran). Patients and Methods: A complete physical examination in the morning with a midstream urine sample collection obtained from 3014 students in two educational areas of Yazd, Iran. Students with positive test results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…Comparing our results to other similar studies revealed that the percentage of hematuria, proteinuria, and UTIs in our data similar to Rao et al [14] and Shen et al [15] reported in China, higher than those reported in by Bakr et al [11] in Dakahlia city in North Egypt, Nodoshan et al [16] in Yazd city in Iran, Parakh et al [17] in India, Zainal et al [18] in Malaysia, and Murakami et al [19] in Tokyo city in Japan, and lower than those reported by Zein El-Abden et al [12] in El-Garbyia city in North Egypt, El-Shafie et al [13] in Monoufiya city in North Egypt, Dang et al [20] in Vietnam, Hajar et al [21] in Lebanon, Oviasu et al [22] in Nigeria, and Plata et al [23] in Bolivia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparing our results to other similar studies revealed that the percentage of hematuria, proteinuria, and UTIs in our data similar to Rao et al [14] and Shen et al [15] reported in China, higher than those reported in by Bakr et al [11] in Dakahlia city in North Egypt, Nodoshan et al [16] in Yazd city in Iran, Parakh et al [17] in India, Zainal et al [18] in Malaysia, and Murakami et al [19] in Tokyo city in Japan, and lower than those reported by Zein El-Abden et al [12] in El-Garbyia city in North Egypt, El-Shafie et al [13] in Monoufiya city in North Egypt, Dang et al [20] in Vietnam, Hajar et al [21] in Lebanon, Oviasu et al [22] in Nigeria, and Plata et al [23] in Bolivia.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that prevalence of urinary abnormities was 1.9% in initial urinary screening and 1.3% in the second screening. The results reported in the second screening were smaller than those reported in the first screening in this study as well as many others studies [11,14,15,16]. Repeat screenings were performed to eliminate false results.…”
Section: Discussioncontrasting
confidence: 70%
“…It was similar to the result from a study in western Saudi Arabia 31 but lower prevalence of 0.69%, 1.5% were reported in Nigeria and Iran respectively. 6,32 The finding of nitrituria in this study may raise the suspicion of urinary tract infections (UTI). However, urine microscopy, culture and sensitivity were not done which was a limitation in this study.…”
Section: Discussionmentioning
confidence: 76%